Klotho (rs1207568 and rs564481) gene variants and colorectal cancer risk - Kamal, Asmaa; Salama, Mohamed; Kamal, Amr; Mohsen, Ahmed; Siam, Ibrahem (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Colorectal cancer is the third commonest cancer worldwide, klotho gene was reported as a tumor suppressor gene, therefore the aim of the present study was to investigate the association between klotho (rs1207568 and rs564481) variants and colorectal cancer (CRC) in Egyptian patients.Materials and Methods: A case-control study comprising 100 patients with CRC and 100 age- and sex-matched healthy controls. Genotyping of klotho was performed by polymerase chain reaction with confronting two-pair primers (PCR-CTPP).Results: The frequencies of the A allele of rs1207568 and the AC haplotype were significantly higher in the CRC patients than in the controls (p=0.019 and 0.005, respectively).Conclusion: We propose that klotho (rs1207568 and rs564481) variants play a significant role in colorectal carcinogenesis and that the klotho protein could be a target for oncotherapy.